The Influence of Job Stress and Work Environment on the Performance of Nusantara High School Teachers in Bandar Lampung - Muhammad Asyrofi; Iskandar AA (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to examine how the work environment and stress affect the effectiveness of teachers at SMA Nusantara Bandar Lampung. Survey research using a quantitative approach is used in this study design. The study focused on teachers at Nusantara High School Bandar Lampung. A saturation sample approach (census) was used to select 41 participants from the population, encompassing principals, teachers, and administrative personnel at Nusantara High School Bandar Lampung. Multiple linear regression analysis is the strategy utilized for data analysis. Primary and secondary data are grouped during the data collection process. A questionnaire was used to collect primary data, and the Likert scale method was employed. Meanwhile, secondary data confirms primary data, which is obtained from interviews and documentation. The study's findings prove that at SMA Nusantara Bandar Lampung, work-related stress and the workplace environment have a major, partial impact on teachers' performance. Concurrently, work-related stress and the work environment have a noteworthy impact on teacher performance at SMA Nusantara Bandar Lampung, ranging from variables of 40.8% to 59.2%, depending on additional factors not covered in the research.